PERANCANGAN BUKU PANDUAN PENDAKIAN GUNUNG ARJUNO VIA TAMBAKSARI SEBAGAI MEDIA INFORMASI - Sonny Ardiansyah; Aditya Rahman Yani; Aileena Solicitor Costa Rica El Chidtian; Wulan W (Jurnal Desain Komunikasi Visual Asia, 2023)
Indonesia is an area that is included in the Pacific Ring of Fire, starting from Sumatra, Java, Bali, Sulawesi, and Papua. There are approximately 400 mountains, about 130 of which are still active. Each mountain has different characteristics and also saves the potential for natural tourism because it has beauty and natural wealth. However, during this pandemic, many natural attractions are closed. One of them is mountain climbing tourism, one of which occurs on Mount Arjuno. The Ministry of Tourism and Creative Economy has made efforts to prepare to increase competence in the new normal era in nature tourism, one of which is the training of mountain tour guide instructors. The training programs that will be implemented include preparing training programs, designing learning media, presenting training materials, and conducting face-to-face training.